The theory “extracted” from the practice of professional educators: writing as a device of lifelong learning - Sisti, Federica (Formazione & insegnamento, 2016)
This work explores the epistemological foundations which guide the analysis of educational practices into a procedure of cognitive research, a training modality based on reflective thought. A strong need to combine the educational practise, acted on the educational field, with the abstract research in university gives the way to think about a new epistemology about practise, which gives importance to situated action, away from the formalised theory, but full of meaning and useful to found a new “practical theory”, a new knowledge base for professional educators who make use of the writing as a means of reflection, self-reflection, cognition and meta-cognition, self-awareness, in order to improve their practise and make themselves more responsible towards their profession.